Energy justice and policy change: An historical political analysis of the German nuclear phase-out. (15th October 2018) - McCauley, Darren; Brown, Antje; Rehner, Robert; Heffron, Raphael; van de Graaff, Shashi
Highlights: Historical institutionalism is applied to energy justice for the first time. Critical junctures provide opportunity windows for policy actors to influence change. Chernobyl is identified as a critical juncture in German nuclear policy. Small businesses are a key driver of energy policy change. Abstract: The German government presented the decision to phase out nuclear energy as a nationally accepted rebalancing of inequality in the energy sector. We expose how this radical change was delivered through a myriad of change agents, most notably through the rise of small energy companies . Critical junctures, in this case the Chernobyl disaster rather than Fukushima, offer moments in time when national policy systems are destabilized. They provide opportunities for changing policy in a perceived pro-energy justice direction if a new consensus can be forged. The paper concludes with a discussion on how energy scholars must engage more with policy analysis frameworks if long-term effective solutions are to be found to persistent energy inequalities.